Stories - Oever, Annie; Christie, Ian (Amsterdam University Press, 2018)
Stories are central drivers of media today-not only do they propel plot-driven entertainment media, such as television, cinema, theatre, but also social media. Telling and having a story is widely deemed essential, both in the large and widely visible world of commerce and in the everyday social lives of individuals. Does this dynamic represent an intensification of what has always been part of culture and civilization, or has it reached a new universality? Stories identifies new phenomena in the fields of complex narration, puzzle film, and transmedia storytelling, and in turn addresses the chief issues of stories and storytelling amid the vast amount of discussion and analysis on the topic, presenting innovative and promising paths forward in research.